Design and Manufacturing Loading Rig Machine for Testing Screw Pile Models - R. Mahmood, Mahmood; H. Humaish, Asad; K. Khalaf, Mustafa (International Journal of Engineering and Technology, 2018)
The main objective of this paper is to design, manufacturing and testing of new loading rig machine to install and testing (i.e. compression and tension load capacity) of screw pile models in both cohesive and cohesionless soil layers. The mainframeÂ was fabricated from thick steel sections, 8mm steel plates that welded together to construct a heavy and strong frame, that able to resist the expected loads during installation (linear and rotational movement at the same time) and testing of the screw pile models (model of loading test). Two independent gearbox motors (actuators) are used to supply the rotational and vertical movement.Â To provide precise control of velocity, the master gearbox motor, that can convert the rotary motion to a linear motion for vertical displacementÂ along two screw bars via two ball screw systems,Â and four stainless guided rods to prevent rotation or inclination the bearing plate (rig) which manufactured from high stiffness stainless-steel was used. The second gearbox motor (â€˜slaveâ€™) mounted on the bottom loading plate that rotates the multi-plate screw pile. It was observed that the measured compression and tension load capacity of screw pile models illustrated the actual behavior of such kind of piles and this machine can be used in both conventional piles (i.e. pipe piles) and screw pile model.Â Â